Efficacy and safety of pioglitazone in patients with ST elevation myocardial infarction treated with primary stent implantation. Issue 13 (24th March 2009) - Kaneda, H; Shiono, T; Miyashita, Y; Takahashi, S; Taketani, Y; Domae, H; Matsumi, J; Mizuno, S; Minami, Y; Sugitatsu, K; Saito, S
Abstract : Background: Recent studies have shown that thiazolidinediones reduce neointimal hyperplasia after bare metal stent (BMS) implantation, but this drug group sometimes cause fluid retention that may lead to heart failure. Objectives: To examine the safety and efficacy of pioglitazone in patients with ST elevation myocardial infarction (STEMI) treated with primary BMS implantation. Methods: Diabetic or non-diabetic patients with STEMI (<12 h from onset) successfully treated with primary BMS implantation were randomised to either the pioglitazone (15 mg, up to 30 mg) or control groups. Patients in cardiogenic shock were excluded. Primary efficacy end point was percentage neointimal volume within the stented segment at 6 months using three-dimensional intravascular ultrasound. Safety end point was a composite of all-cause mortality, reinfarction, or heart failure requiring hospitalisation. Results: Between October 2005 and July 2007, 96 patients were randomised into the pioglitazone (n = 48) or control group (n = 48). At follow-up, mean (SD) percentage neointimal volume and neointimal volume index were significantly reduced in the pioglitazone group (22 (13)% vs 28 (13)%, p = 0.04; 1.5 (0.9) vs 2.0 (0.8) mm 3 /mm, p = 0.02, respectively). During 6 months, two control patients died, four patients (one in the pioglitazone group, three controls) had stent thrombosis resulting in reinfarction and three patients (two in the pioglitazone group, one control) had heart failure, resulting in a similar incidence of safety end point (3 vs 6). Conclusions: Treatment of pioglitazone reduced neointimal hyperplasia in patients with STEMI treated with primary stent implantation without placing the patient at increased risk of complications. Additional larger trials will be necessary to establish the clinical benefit of pioglitazone.